Participation and Postponed Retirement in Central and Eastern Europe - Rob́ert Ivań Gaĺ; Maŕta Rado\' (Hungarian Demographic Research Institute, 2019)
This paper shows how the effective retirement age rose in eight countries of Central and Eastern Europe (Estonia, Latvia, Lithuania, Poland, the Czech Republic, Slovakia, Hungary, and Slovenia) between the mid-1990s and the mid-2010s. It finds that the increase was fast enough to keep life expectancies at the effective retirement age practically unchanged. Every day an average worker of the region got closer to the effective retirement age by only 18.4 hours, instead of 24, because the effective retirement age was moving. In effect, the labor market absorbed all improvements in life expectancies in older working ages. The paper also shows how the educational composition in older working age, specifically in the 55-64-year-old age bracket, improved over the same period, establishing the growth of the effective retirement age. This relatively recent shift is traced back to human capital investments made decades before, specifically the spread of secondary education starting in the 1960s. Finally, the paper shows that maintaining the current life expectancies at retirement over the next 30 years requires less effort in terms of further raising the effective retirement age than what the region achieved in this respect in the last 15 years. Since the countries discussed improved their education systems in recent decades by expanding tertiary enrollment among currently young cohorts, an additional increase in the effective retirement age in the future can be expected, possibly even fending off most of the potentially negative effects of declining mortality.
Keywords: N34; J13; J14; 300; effective retirement age; expansion of education; period and cohort life expectancy; Central and Eastern Europe; Altersgrenze; Sterblichkeit; Schätzung; Osteuropa; EU-Staaten